The Mitogenomic Characterization and Phylogenetic Analysis of the Plant Pathogen Phyllosticta yuccae - Xu, Hui; Zhu, Ziyi; Tian, Zeyuan; Wei, Cuiyuan; Fan, Qi; Wang, Yuanbing; Shen, Shikang; Deng, Gang; Ding, Mingliang (Genes, 2024)
Phyllosticta yuccae is an important plant pathogen causing leaf spot disease in Yucca gigantea Lem. It is imperative to note that the amount of information available about the mitogenome of this subject is severely limited. This must be addressed immediately, as it is crucial to our understanding and progress in this field. To better understand the mitogenomic characteristics of P. yuccae, we conducted its sequencing by MGISEQ. Afterwards, the mitogenome was assembled and annotated. The mitogenomic characteristics and phylogenetic placement of the P. yuccae strain KUMCC 6213 were analyzed. The study revealed that the mitogenome of P. yuccae is a circular DNA molecule, consisting of 178,540 base pairs. It contains a total of 64 genes, including 14 protein-coding genes (PCGs), 26 transfer RNA genes (tRNA), 2 ribosomal RNA genes (rRNA), and 22 open reading frame genes (ORF), accounting for 80.98% of the total size. Repetitive sequences accounted for 15.42% of the mitogenome. The analysis of codon usage indicated that the codon UUA was the most commonly utilized, whereas the amino acid Leu was the most frequently employed. A comparative analysis of mitogenomes between P. yuccae and Macrophomina phaseolina (Tassi) Goid. showed notable variations in the position and size of gene clusters, with cox1, nad4, and nad4L genes exhibiting relatively low conservation. Phylogenetic analysis based on the 14 PCGs revealed that P. yuccae has the closest genetic relationship with M. phaseolina (Botryosphaeriaceae, Botryosphaeriales). This study first reports the mitogenome of P. yuccae and validates its phylogenetic placement. The findings enhance the knowledge of mitogenomes in Botryosphaeriales, offering novel perspectives on the genetics and evolution of the plant pathogen P. yuccae. This is crucial for the accurate prevention and management of leaf spot disease in Y. gigantea.